2019
DOI: 10.1136/postgradmedj-2018-136364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E in non-alcoholic fatty liver disease: a systematic review and meta-analysis of randomised controlled trials

Abstract: The efficacy of vitamin E among patients with non-alcoholic fatty liver disease (NAFLD) is unclear. The current qualitative and quantitative analyses aimed to ascertain the efficacy of vitamin E on clinical outcomes of patients with NAFLD. A systematic search of randomised controlled trials (RCTs) was performed using databases (PubMed, ProQuest, Scopus, EBSCOhost and Ovid) from inception to July 2018. Trials meeting the inclusion criteria were subjected to quality assessment using the Jadad Scoring. All trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 24 publications
1
62
2
16
Order By: Relevance
“…Adjuvant Vitamin E therapy has been shown to be efficacious in adults with NAFLD, however a similar significant effect has not been demonstrated on meta-analysis in paediatric patients [63]. Vitamin E therefore remains unlicensed for this indication in the United Kingdom, although may be considered for children with advanced liver fibrosis in tertiary care settings [64].…”
Section: Anti-oxidantsmentioning
confidence: 99%
“…Adjuvant Vitamin E therapy has been shown to be efficacious in adults with NAFLD, however a similar significant effect has not been demonstrated on meta-analysis in paediatric patients [63]. Vitamin E therefore remains unlicensed for this indication in the United Kingdom, although may be considered for children with advanced liver fibrosis in tertiary care settings [64].…”
Section: Anti-oxidantsmentioning
confidence: 99%
“…Despite the potential benefits of vitamin E for the treatment of NAFLD and the randomized controlled trials (RCTs) conducted to validate this fact, there is a lack of systematic reviews that could help conclude these studies. There has been some work where authors have looked at the effects of vitamin E among all population groups [11]. However, there exists a great deal of disproportionation between the prevalence of NAFLD among different age groups, with the disease becoming more prevalent in the aging population [12].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria. We included eligible studies that met the following criteria: (1) randomized controlled clinical trials, (2) studies that conducted on adult subjects (≥ 18 years), (3) studies that administered vitamin E in different chemical forms including alpha-, beta-, gamma-, and delta-tocopherol and alpha-, beta-, gamma-, and delta-tocotrienol, (4) RCTs with at least one week's duration of intervention, and (5) controlled trials that reported mean changes and their standard deviations (SDs) of inflammatory cytokines throughout the trial for both intervention and control groups or presented required information for calculation of those effect sizes. If > 1 article were published for one dataset, the more complete one was included.…”
mentioning
confidence: 99%